MECHANICAL PROPERTIES OF FIBER WASTE TIRE CONCRETE - Battal Najim, Khalid (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT: Many of researchers study the uses of chopped worn-out tires as a replacement material to production special types of concrete. In presented work, the worn-out tires were used as fibers which have dimensions of 1×1×3 cm. The fibers used as a partial replacement from volume of coarse aggregate. Two mixes of fiber worn-out tires (F.W.T.) concrete in addition to reference mix were selected, using Partial Replacement Ratio (PRR) of 20% and 30%. The tests which were used in this study were: compressive strength, splitting tensile strength and flexural strength. It was found that incorporating of F.W.T. in concrete effected negatively on most properties of concrete, for example the percentage decreases in compressive strength relative to reference mix at 28 day were 20% and 27.3% for concrete with 20% and 30% F.W.T. by volume of coarse aggregate respectively. However, it gave good indicator to be utilized as a new construction material in many applications.